Anesthesia-related cardiac arrest in children: The Thai anesthesia incidents study (THAI study) - Bunchungmongkol N. (2014)
Background and Objective: The Thai Anesthesia Incidents study (THAI Study) is the first national study of anesthesia outcomes during anesthesia practice in Thailand. The authors extracted data of 25,098 pediatric cases from the THAI Study in order to examine the incidence, suspected causes, contributory factors, and suggested corrective strategies associated with anesthesia-related cardiac arrest. Material and Method: A multi-centered prospective descriptive study was conducted among 20 hospitals across Thailand over a year between March 1, 2003 and February 28, 2004. Data of cardiac arrests in children aged 15 years and younger were collected during anesthesia, in the recovery room and 24 hours postoperative period, and reviewed independently by at least two reviewers. Results: Incidence of anesthesia- related cardiac arrest was 5.1 per 10,000 anesthetics, with 46% mortality rate. Infants accounted for 61% of cases. Incidences of overall cardiac arrest and anesthesia-related arrest were significantly higher in infants than older children and in children with ASA physical status 3-5 than those with ASA physical status 1-2. Most of the anesthesia-related arrests occurred in the operating room (61%) during induction or maintenance of anesthesia (84%). Respiratory-related cardiac arrest was the most common suspected cause of anesthesia-related cardiac arrest. Improving supervision, additional training, practice guidelines, efficient blood bank, equipment maintenance, and quality assurance monitoring are suggested corrective strategies to improve the quality of care in pediatric anesthesia. Conclusion: The incidence of anesthesia-related cardiac arrest was 5.1:10,000 anesthetics. Major risk factors were children younger than 1 year of age and ASA 3-5. The identifications of airway management and medication-related problems as the main causes of anesthesia-related cardiac arrest have important implications for preventive strategies.